Pyrene monomer-excimer dynamics to reveal molecular organization in mesoporous hybrid silica films - Kusz, Jakub; Boissiere, Cédric; Bretonnière, Yann; Sanchez, Clément; Parola, Stephane (Nanoscale, 2024)
Self-assembly and characteristics of hybrid mesoporous silica film templates remain a subject of inquiry. The short time scale of the inorganic condensation and formation of micelles makes our understanding of this process insufficient. To provide an insight into the evaporation-induced self-assembly of such films, we synthesized an efficient molecular probe of the triethoxysilane precursor bearing a pyrene derivative. The probe was introduced into the porous film at the synthesis stage through the sol-gel co-condensation method. At different synthesis stages, the emission of pyrene moieties was measured by fluorescence spectroscopy, revealing the placement of probes within the film. We also report dynamic excimer formation upon template removal. Moreover, we evaluate the influence of several parameters on the pyrene excimer formation phenomenon. The pore geometry, probe concentration, and the presence of another organosilane precursor are investigated in this work. Pyrene derivative is used as a molecular probe to investigate the interactions in hybrid mesoporous films through fluorescence spectroscopy. The dynamic formation of pyrene excimer provides insight into the nanoscale organization of the material.